An evaluation of Ni-Alumina composite electroplating on mild steel - Norlida, Jamil (2010)
This thesis deals with an evaluation of Ni- Alumina composite electroplating on mild steel. Electroplating process has been carried out by utilizing the Watt’s Bath with Alumina oxides powder. Weight changes in both electrode shows that weight loss of anode and weight of deposit on cathode are proportional to plating time and voltage supplied. There are three parameters involve in this project that are Alumina concentration, plating time, and voltage supplied. Mild steel will be the anode and connected to positive terminal. Meanwhile, nickel plate as anode will be connected to negative terminal. Dimension of sample in this project is 80 mm x 30 mm x 1.5 mm. Nickel ion is reduced to form or plate a surface on mild steel. The electroplating bath contains the metal ion to be reduce as well as Alumina oxides to support the flow of electrons. While reduction of the metal occurs at cathode, oxidation is simultaneously occurring at anode. After that, microstructural analysis was done to observe the thickness of coating and its surface structure. Lastly, all the samples were undergoes Vickers hardness test. In this project, it can be conclude that result shows increase of Alumina concentration, plating time, and voltage supplied also increase the thickness of coating.